What happens to opiate addicts immediately after treatment: a prospective follow up study. Issue 6584 (30th May 1987) - Gossop, M; Green, L; Phillips, G; Bradley, B
Abstract : In the first British study to investigate systematically what happens to opiate addicts after treatment 50 opiate addicts admitted for inpatient treatment of their drug dependence were followed up for six months after discharge. All had been withdrawn from opiates before follow up. Six months later 26 were not using opiates: 12 had not used opiates at any time since discharge. When subjects in hospital or in prison were excluded from the analysis 21 (47%) of the subjects living in the community were not taking opiates. Many subjects used opiates within days of leaving the inpatient unit, but this first lapse did not necessarily lead to a full relapse into addictive use. During the six months after discharge several subjects used opiates on a less than daily basis. During each two month period throughout the six months of follow up the proportion of subjects who were occasional users fell, the proportion of abstinent subjects grew, and the proportion of daily users (assumed to be readdicted) remained constant. Although many of the addicts relapsed soon after treatment, it was encouraging that almost half were opiate free after six months. These results have important implications for the treatment of drug addicts.